Liming and lime-phosphorus-zinc interactions in two Nigerian Ultisols: I. Interactions in the soil - Friesen, Dennis K.; Juo, A.S.R.; Miller, M.H. (Wiley, 1980)
Interactions of lime, phosphorus (P), and zinc (Zn) in two coarse-textured Ultisols from southeastern Nigeria were examined by means of factorial soil incubation and phosphate sorption experiments. In both soils, liming reduced exchangeable aluminum (Al) saturation from 45% to < 5% at pH 5.0 and soil solution Al concentration to < 1.0 µg/ml also near pH 5.0. There was no significant lime-P interaction on active Al levels, indicating a lack of any ameliorating value of P on Al toxicity. Adsorption isotherms showed that liming reduced P adsorption in both soils at equilibrium solution concentrations of approximately 0.2 µg P/ml or higher, but at lower concentrations the effect became inconsistent. Soil incubation studies indicated that the concentration of P in soil solution (null-point estimate) was first reduced by lower rates of lime then increased when soils were limed to approximately pH 6.0 or higher. Zinc activity in soil solution declined sharply when soils were limed to pH above 5.0, but was unaffected by P applications within the pH range studied (pH 4.3 to 7.2).